Tuberculous cystitis - Mallick, MS (Mediscope, 2017)
Pulmonary tuberculosis is very common but genitourinary tuberculosis, specifically tuberculous cystitis is very rare. A 40 year old male patient came to a teaching hospital on 26 June 2016 with the complaints of fever, painful micturition, haematuria, lower abdominal pain and gradual loss of weight. The case was diagnosed as tuberculous cystitis and treated accordingly and successfully. In this report, the case condition, procedure of diagnosis and treatment are reported in details. Mediscope Vol. 4, No. 2: Jul 2017, Page 35-38